Anorexia Reduces GFAP+ Cell Density in the Rat Hippocampus. (7th August 2016) - Reyes-Haro, Daniel; Labrada-Moncada, Francisco Emmanuel; Varman, Durairaj Ragu; Krüger, Janina; Morales, Teresa; Miledi, Ricardo; Martínez-Torres, Ataúlfo
Abstract : Anorexia nervosa is an eating disorder observed primarily in young women. The neurobiology of the disorder is unknown but recently magnetic resonance imaging showed a volume reduction of the hippocampus in anorexic patients. Dehydration-induced anorexia (DIA) is a murine model that mimics core features of this disorder, including severe weight loss due to voluntary reduction in food intake. The energy supply to the brain is mediated by astrocytes, but whether their density is compromised by anorexia is unknown. Thus, the aim of this study was to estimate GFAP+ cell density in the main regions of the hippocampus (CA1, CA2, CA3, and dentate gyrus) in the DIA model. Our results showed that GFAP+ cell density was significantly reduced (~20%) in all regions of the hippocampus, except in CA1. Interestingly, DIA significantly reduced the GFAP+ cells/nuclei ratio in CA2 (−23%) and dentate gyrus (−48%). The reduction of GFAP+ cell density was in agreement with a lower expression of GFAP protein. Additionally, anorexia increased the expression of the intermediate filaments vimentin and nestin. Accordingly, anorexia increased the number of reactive astrocytes in CA2 and dentate gyrus more than twofold. We conclude that anorexia reduces the hippocampal GFAP+ cell density and increases vimentin and nestin expression.